Synthesis of water‐soluble phthalocyanines containing 1‐methyl‐1H‐imidazole‐2‐thiol: Investigation of DNA nuclease, α‐glucosidase inhibitory, and photo‐physicochemical properties. (14th February 2021) - Günsel, Armağan; Kalkan, Fatma; Atmaca, Göknur Yaşa; Barut, Burak; Bilgiçli, Ahmet T.; Pişkin, Hasan; Özel, Arzu; Erdoğmuş, Ali; Yarasir, M. Nilüfer
Abstract : In this work, we have presented on the synthesis and characterization of novel 3‐(1‐methyl‐1 H ‐imidazole‐2‐thiol)phthalonitrile (1 ) as a ligand and its nonperipherally (M = 2H (2 ), Zn(II) (3 ), and GaCl(III) (4 )) phthalocyanines and their highly water‐soluble hydrochloride derivatives (2a–4a ), containing 1‐methyl‐1 H ‐imidazole‐2‐thiol substituents. All compounds were supported by FT‐IR, UV–Vis, 1 H‐NMR, 13 C‐NMR, and MALDI‐TOF mass spectra. The molecular structure of the novel compound (1 ) and its intermolecular interactions have been elucidated by analyzing the results of X‐ray diffraction measurements. In order to determine the supercoiled pBR322 plasmid DNA nuclease properties of compounds (2a–4a ), agarose gel electrophoresis was used. The plasmid DNA nuclease did not observe without light irradiation on increasing concentrations (2a–4a ). When irradiated at 10 and 20 J/cm 2, the band intensities changed on agarose gel, displaying photonuclease activity on supercoiled pBR322 plasmid DNA of compounds (2a–4a ); 4a had the highest photonuclease activities in a concentration‐dependent manner at 10 and 20 J/cm 2 . The in vitro α‐glucosidase inhibitory effects of compounds (2a–4a ) were investigated to determine whether they can be used in potential agents for diabetes mellitus. Compounds (2a–4a ) showed higher inhibitory effects than acarbose (63.03 ± 2.14 μM) against α‐glucosidase enzyme. Lineweaver–Burk analysis showed that K m increased and V max remained the same on increasing concentrations of compounds (2a–4a ). The finding results claimed that the compounds inhibited α‐glucosidase enzyme via competitive manner. Dixon plots showed that K i values of compounds (2a–4a ) were 14.70 ± 0.70, 11.20 ± 0.50, and 12.60 ± 0.20 μM, respectively. Besides, the effect of including metal ion on photochemical and photophysical features of the compounds was studied in DMSO and water, comparatively. The compounds gave high singlet oxygen quantum yields (ΦΔ = 0.86 for (4a ), 0.77 for (3a ), and 0.59 for (2a )) in DMSO. The results showed that the compounds are also very suitable for photodynamic therapy applications. Abstract : In this work, we have presented on the synthesis and characterization of novel 3‐(1‐methyl‐1 H ‐imidazole‐2‐thiol) phthalonitrile (1 ) as a ligand and its non‐peripherally [M=2H (2 ), Zn(II) (3 ), GaCl(III) (4 )] phthalocyanines and their water‐soluble hydrochloride derivatives (2a‐4a ), containing 1‐methyl‐1 H ‐imidazole‐2‐thiol substituents. The molecular structure of the novel compound (1 ) and its intermolecular interactions have been elucidated by analysing the results of x‐ray diffraction measurements. Then, we have investigated DNA nuclease, α‐glucosidase inhibitory and photo‐physicochemical properties.